2021
DOI: 10.3390/nu13020546
|View full text |Cite
|
Sign up to set email alerts
|

Folate and Cobalamin Serum Levels in Healthy Children and Adolescents and Their Association with Age, Sex, BMI and Socioeconomic Status

Abstract: This study proposes age- and sex-specific percentiles for serum cobalamin and folate, and analyzes the effects of sex, age, body mass index (BMI), and socioeconomic status (SES) on cobalamin and folate concentrations in healthy children and adolescents. In total, 4478 serum samples provided by healthy participants (2 months–18.0 years) in the LIFE (Leipzig Research Centre for Civilization Diseases) Child population-based cohort study between 2011 and 2015 were analyzed by electrochemiluminescence immunoassay (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 45 publications
1
12
0
1
Order By: Relevance
“…A recent study reported that serum folate is inversely correlated with BMI in healthy adolescents [20].…”
Section: Discussionmentioning
confidence: 98%
“…A recent study reported that serum folate is inversely correlated with BMI in healthy adolescents [20].…”
Section: Discussionmentioning
confidence: 98%
“…The BMI-SDS was calculated using BMI, sex, and age in months to assess the BMI in an age- and sex-dependent manner, as described in details previously [ 16 ]. The patients were classified as underweight (BMI-SDS < − 1.28), normal weight (BMI-SDS − 1.28 to 1.279), and overweight or obesity (BMI-SDS ≥ 1.28) [ 17 , 18 ]. The CCCs were calculated based on the number of diseases among 12 disease categories to adjust for the severity of comorbidities on admission, as previously described [ 15 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies on optimal serum concentrations in healthy European children are still scarce, and no universally accepted cut-offs have been established [ 87 ].…”
Section: Micronutrients Deficiency In Childhood Obesitymentioning
confidence: 99%